OPTIMALISASI TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI ERA DIGITAL - Putra, Ikhsan Maulana; Raja Bani Pilitan; Refril Dani; Kurniawan (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to analyze the optimization of technology in physical education learning in the digital era among students of the Physical Education Study Program at Muhammadiyah University of Muara Bungo. The urgency of this research is based on the need to adapt practical learning methods towards digital platforms to enhance effectiveness in higher education. This research employs a qualitative approach with a descriptive method. The research informants consisted of 57 students selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, documentation, and literature review.The results show that the use of technology such as learning videos, online learning platforms, and fitness applications can increase learning motivation, facilitate understanding of practical materials, increase participation, and facilitate the learning evaluation process. However, the implementation of technology still faces obstac The results show that the use of instructional videos, Google Classroom, YouTube, and fitness applications can significantly increase students' motivation, participation, and understanding of motor skills. The study concludes that although technology greatly assists in evaluation and independent learning, its implementation is still hindered by limited network infrastructure and digital literacy. Keywords: Educational Technology; Digital Era; Physical Education; Learning Optimization.